A introduç\~ao de novas tecnologias nos veículos e a reduç\~ao da sinistralidade no trânsito - Paulo César Pêgas Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper presents a detailed analysis of claims that occurred on Brazilian federal highways, in the years 2020 and 2021, registered by the Federal Highway Police (PRF), segmented by brand, year of manufacture and model, to establish a severity criterion from of these characteristics. To mitigate possible impacts related to the different volumes of sales of each model, in different years, these numbers are represented in the form of apportionment for every 100,000 licensed vehicles. Another factor analysed and inserted consists of the difference in mileage round, by each model and per year of manufacture, which resulted in the creation of an "adjustment factor" by brand, year and model. It came from real market data, obtained by information from vehicles announced and marketed throughout the country, as well as consolidation of data related to the review of new and new vehicles in workshops of authorized networks-which is already an unprecedented parameter in published studies. It is relevant, however, to emphasize that: by combining the severity, apportioned by 100,000 licensed vehicles, adjusted to the average mileage round, per brand, year and model, a new methodology of ratification or rectification of Crash Tests indicators was generated. Thus, this study becomes a robust work on argument about the evolution of active and passive security technology in new models sold in Brazil and, even more important, about the effectiveness, efficiency and effectiveness of tax incentives and subsidies granted to automakers by the Government of Brazil.
Keywords: L62; O14; O35; R41; 330; technology; production; vehicle safety; traffic safety